NON-INVASIVE ASSESSMENT OF ANTI-SEIZURE DRUGS AND THEIR ABILITY TO PREVENT EPILEPTIFORM CHANGES - Paronikyan, R. G.; Sarkisyan, R. Sh; Avagyan, M. N.; Grigoryan, M. S.; Paronikyan, A. D. (Èpilepsiâ i paroksizmalʹnye sostoâniâ (Online), 2018)
The aim of the study is the assessment of possibility of using «Bioscope» device to detect the direction of changes in the integrative state of organism of rats under the influence of analeptic and convulsive agent of corazole, and known anticonvulsant medicaments the Phenobarbital, luminal, and diazepam. Materials and methods. Six series of experiments were performed with a 90-minute recording of integrative state of animals in the norm, after injection of corazol (50 mg/kg, subcutaneously), after injection of luminal (40 mg/kg, intraperitoneally) and diazepam (2 mg/kg, intraperitoneally), as well as after combined injection of luminal and corazole, diazepam and corazole. To record and analyze the signals of Bioscope device, a comprehensive software package was developed in the LabView software environment. Results. Signals of «Bioscope» device are changed differently after injection of corazole, luminal or diazepam. At the same time, among all used indicators, the spectral distribution of BB-intervals of «Bioscope» signals turned out to be the most sensitive to different experimental conditions. After injection of corazole, a pronounced peak in the frequency range of 0.3 osc/min is formed in the spectral distribution of inter-peak BB-intervals, which, perhaps, reflects the epileptiform state of the animal’s organism. After combined injection of luminal and corazole, as well as diazepam and corazole, the spectral distribution of inter-peak BB-intervals approaches the control type, which indicates the effectiveness of used anticonvulsants medicaments. Conclusion. The conducted research revealed the expediency of using the «Bioscope» device complex for rapid assessment of the type and dose of anticonvulsant medicaments for inerruption of epileptiform states of the organism.